2020
DOI: 10.1002/bse.2676
|View full text |Cite
|
Sign up to set email alerts
|

Do independent, female and specialist directors promote eco‐innovation and eco‐design in agri‐food firms?

Abstract: Eco‐innovation and eco‐design strategies are associated with firms' innovation capabilities. Moreover, they may impact on access to public subsidies and on financial performance. In this respect, the agri‐food industry is especially vulnerable, because in general, this sector has less experience of technological innovation, and managers are more likely to be averse to such projects. On the other hand, the board may promote a proactive environmental approach to defend the interests of investors and other stakeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 110 publications
3
70
3
Order By: Relevance
“…Furthermore, eco-innovation investments are also strengthened by regulatory pressure at national and sectoral level as well as by the existence of a CSR committee on the board of directors. In this case, our results contrast with those obtained by García-Sánchez et al (2021), who found a positive but not statistically significant effect of the existence of a CSR committee on eco-innovation.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, eco-innovation investments are also strengthened by regulatory pressure at national and sectoral level as well as by the existence of a CSR committee on the board of directors. In this case, our results contrast with those obtained by García-Sánchez et al (2021), who found a positive but not statistically significant effect of the existence of a CSR committee on eco-innovation.…”
Section: Resultscontrasting
confidence: 99%
“…Regarding the control variables, following previous studies (García-Sánchez et al 2020a;García-Sánchez et al 2020b;García-Sánchez et al 2021), we have included a broad set of control variables representing the firm's capabilities and resources, monitoring mechanisms, and institutional pressures. The inclusion of these variables allows us to avoid biased results because of the impact they have on the development of proactive environmental strategies by companies.…”
Section: Models and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results for the relationship of interest are also shown. [27,47,85,89] Use of resources [27,71,85] Emissions [19,47,72,85,[90][91][92] Environmental innovation [30,31,93,94] Environmental performance Negative relationship [87] Consumption of water and energy [95] Environmental innovation [28,34,[96][97][98][99][100][101][102][103][104][105][106] Environmental performance No relationship [29] Consumption of energy [27,85] Environmental innovation Source: authors, based on the literature review.…”
Section: Board Gender Diversity and Environmental Performancementioning
confidence: 99%
“…Enterprises should not be developed at the cost of the ecological environment [17]. Enterprises must abide by relevant laws and regulations and protect the ecological environment [18,19].…”
Section: Literature Review and Hypotheses Development 21 Literaturementioning
confidence: 99%